Do human capital investments mediate the intergenerational transmission of domestic violence? - Jorge M. Agüero; Catalina Herrera-Almanza; Kira Villa (Elsevier, 2022)
Background: Domestic violence is a major public health issue worldwide with detrimental consequences not only for its victims but also for the next generations. Despite an extensive literature documenting the persistent intergenerational transmission of domestic violence, few studies explore the mechanisms underlying this transmission. Methods: We use data from the Cebu Longitudinal Health and Nutrition Survey implemented between 1984 and 2009 in the Philippines. These longitudinal data allow us to measure how much the association between witnessing parental violence during childhood and the experience of intimate partner violence in young adulthood is explained by different measures of human capital that occur up to young adulthood, including education and health outcomes, cognitive skills, and psychosocial traits. Results: We find that these human capital measures explain 22 percent of the transmission of domestic violence. Our results indicate that depression at age 18 and cognitive ability at age 11 are the primary human capital channels. Conclusions: Our findings suggest a potential role of interventions targeting these human capital investments in reducing the cycle of violence across generations, as such, it could expand the window of opportunity for effective interventions in developing countries.